The precession of SS433's radio ruff on long timescales - Doolin, S; Blundell, K (Institute of Physics Publishing, 2009)
Roughly perpendicular to SS433's famous precessing jets is an outflowing "ruff" of radio-emitting plasma, revealed by direct imaging on milli-arcsecond scales. Over the last decade, images of the ruff reveal that its orientation changes over time with respect to a fixed sky co-ordinate grid. For example, during two months of daily observations with the VLBA by Mioduszewski et al. (2004), a steady rotation through ~10 degrees is observed whilst the jet angle changes by ~20 degrees. The ruff reorientation is not coupled with the well-known precession of SS433's radio jets, as the ruff orientation varies across a range of 69 degrees whilst the jet angle varies across 40 degrees, and on greatly differing and non-commensurate timescales. It has been proposed that the ruff is fed by SS433's circumbinary disk, discovered by a sequence of optical spectroscopy by Blundell et al. (2008), and so we present the results of 3D numerical simulations of circumbinary orbits. These simulations show precession in the longitude of the ascending node of all inclined circumbinary orbits - an effect which would be manifested as the observed ruff reorientation. Matching the rate of ruff precession is possible if circumbinary components are sufficiently close to the binary system, but only if the binary mass fraction is close to equality and the binary eccentricity is non-zero.